2010
DOI: 10.1111/j.1365-3156.2010.02675.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs and outcomes of VCT delivery models in the context of scaling up services in Indonesia

Abstract: Summaryobjective To evaluate costs and outcomes of voluntary counselling and testing (VCT) service delivery models in urban Indonesia.methods We collected primary data on utilization, costs and outcomes of VCT services in a hospital clinic (568 clients), HIV community clinic (28 clients), sexually transmitted infection (STI) community clinic (784 clients) and prison clinic (574 clients) in Bandung, Indonesia, in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…Routine HIV testing in a prison setting was found to be cost-effective in the USA . Also for Indonesia, where the present study was conducted, the unit cost of counseling and testing in prisons was lower compared to other settings such as hospital-based clinics or STI/HIV community clinics, while enrollment rates in HIV care were higher (Siregar et al, 2011). Still, prisons in many countries lack the necessary resources and staff to implement routine screening for HIV infection.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Routine HIV testing in a prison setting was found to be cost-effective in the USA . Also for Indonesia, where the present study was conducted, the unit cost of counseling and testing in prisons was lower compared to other settings such as hospital-based clinics or STI/HIV community clinics, while enrollment rates in HIV care were higher (Siregar et al, 2011). Still, prisons in many countries lack the necessary resources and staff to implement routine screening for HIV infection.…”
Section: Introductionmentioning
confidence: 86%
“…To determine costs of screening, we used the unit cost of 23 USD for HIV testing from the health provider's perspective as determined in a recent health-economic study in the same prison (Siregar et al, 2011). The total cost during routine or targeted screening was calculated by multiplying the total number of inmates tested by the unit cost of 23 USD.…”
Section: Estimation Of the Screening Costsmentioning
confidence: 99%
“…It found that on average, unit costs decreased with scale, but also that high levels of inefficiency were similar at any scale [ 11 ]. Since PANCEA, a number of empirical studies have found important differences in the unit cost of HTC across facilities and service delivery models in several countries including Kenya [ 12 ], Swaziland [ 12 ], Nigeria [ 13 ], Zambia [ 14 ], and Indonesia [ 15 ]. Studies comparing the unit cost of PMTCT across facilities in India [ 16 ] and Zambia [ 14 ] also found a great deal of variation.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, compared to previous studies on Klinik Mawar, unit costs for mobile VCT appeared to be lower than for clinic-based VCT (US$65). 22 In addition, the mobile intervention's eff seemed positive. Increasing mobile VCT coverage may therefore be more feasible compared to the inclinic programme.…”
Section: Discussionmentioning
confidence: 99%